2010
DOI: 10.1029/2010jd014771
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption spectra, radiative efficiencies, and global warming potentials of perfluorocarbons: Comparison between experiment and theory

Abstract: Experimentally and theoretically determined infrared spectra are reported for a series of straight‐chain perfluorocarbons: C2F6, C3F8, C4F10, C5F12, C6F14, and C8F18. Theoretical spectra were determined using both density functional (DFT) and ab initio methods. Radiative efficiencies (REs) were determined using the method of Pinnock et al. (1995) and combined with atmospheric lifetimes from the literature to determine global warming potentials (GWPs). Theoretically determined absorption cross sections were wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
135
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(150 citation statements)
references
References 31 publications
13
135
2
Order By: Relevance
“…The sample (2) should be placed in the focus of the parabolic mirror (the focal length f = 2 cm). It is very difficult to create a cryostat with linear sizes allowing to place the sample into the mirror focus, so we used a light guide for transferring the focus from the sample cell (12) to the sample place (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample (2) should be placed in the focus of the parabolic mirror (the focal length f = 2 cm). It is very difficult to create a cryostat with linear sizes allowing to place the sample into the mirror focus, so we used a light guide for transferring the focus from the sample cell (12) to the sample place (2).…”
Section: Methodsmentioning
confidence: 99%
“…One end of the light guide is placed inside the working volume (12), the other in the focus of the parabolic mirror (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature value measured for the 900-1900 cm -1 interval was reported by Goto et al (2002), and it is 16% lower than the predicted here, 0.37 vs 0.43. However, differences within 14-25% of existing experimental values provide a valuable data for the REs in order to calculate accurate GWPs values (Blowers et al, 2007;Bravo et al, 2010b). Another advantage of using computational techniques to predict REs and hence GWPs, is the possibility of evaluate the cross-section spectrum over the overall infrared spectral interval, 0-2500 cm -1 , since the range of 0-700 cm -1 is difficult to measure using commercial infrared spectrometers.…”
Section: Strategies To Design Cfc Alternatives With Low Environmentalmentioning
confidence: 99%
“…In this way, recent researches have indicated that it is possible to calculate infrared spectra using ab initio and DFT (Density Functional Theory) methods with useful accuracy, and that radiative transfer models can then be applied to these spectra to determine radiative efficiencies and hence GWPs [Papasavva et al, 1997;Blowers et al, 2007;Bera et al, 2010;etc..]. In the method performed by Bravo et al (2010b) theoretical spectra for a set of perfluorocarbons were determined using DFT methods. Then, the radiative efficiencies (REs) were determined using the method of Pinnock et al (1995) and combined with atmospheric lifetimes from the literature to determine global warming potentials (GWPs).…”
Section: Strategies To Design Cfc Alternatives With Low Environmentalmentioning
confidence: 99%